Resynchronizing Returns to Estrus after a Prior Insemination - J. S. Stevenson; J. A. Sauls-Hiesterman (Kansas Agricultural Experiment Station Research Reports, 2020)
In two experiments, GnRH and a progesterone insert (CIDR) were applied to cows after insemination (day 0) to reprogram or synchronize the returning estrus of cows that failed to conceive to that previous insemination. The combination of GnRH (day 14) and a CIDR insert (days 17 to 24) in experiment 1 (n = 347 cows) increased the proportion of nonpregnant cows returning to estrus before pregnancy diagnosis on day 32 by 7.4 percentage points, increased the synchrony of their return by 24.4 percentage points, but delayed that return by 2.3 days compared with controls. In experiment 2 (n = 863 cows), use of GnRH alone (day 7), a CIDR insert alone (days 14 to 21), or in combination, failed to increase the proportion of nonpregnant cows in estrus before pregnancy diagnosis on day 32, but cows receiving the CIDR insert had increased synchrony of estrus by 24 to 34 percentage points compared with cows that did not receive a CIDR insert. In both experiments, the treatment of cows with GnRH or GnRH + CIDR insert increased the pretreatment pregnancy rate by 7.1 to 9.5 percentage points. We conclude that administering GnRH with or without a CIDR insert to resynchronize returns to estrus did not significantly improve the proportion of nonpregnant cows reinseminated before pregnancy diagnosis.
Keywords: estrus; CIDR; GnRH; dairy cow